2002
DOI: 10.1348/135910702320645408
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol control, medication adherence and illness cognition

Abstract: Objective. To examine the relation between illness cognitions and two measures of adherence in patients with hypercholesterolaemia, a disease marked by chronically high cholesterol.Design. Cross-sectional. Based on the self-regulation model (Leventhal, Diefenbach, & Leventhal, 1992), patients' illness cognitions were predicted to be related to cholesterol control and medication adherence. Patients with illness cognitions consonant with an experts' mental model of hypercholesterolaemia were expected to show bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
5
44
1
2
Order By: Relevance
“…Patients who have models that differ from medical models of hypertension have been shown to have poorer compliance and higher BPs. 15 We did not find any signficant relationships between cause perceptions and compliance however.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Patients who have models that differ from medical models of hypertension have been shown to have poorer compliance and higher BPs. 15 We did not find any signficant relationships between cause perceptions and compliance however.…”
Section: Discussioncontrasting
confidence: 51%
“…14 Identity, consequence and specific-necessity were found to relate to compliance in a cohort of haemophiliacs. 15 Again, consequence beliefs were found to predict compliance in a study of patients with hypercholesterolaemia. 16 A recent meta-analysis that looked at studies using the self-regulatory model, but not necessarily the IPQ, showed a correlation between specific problem focused coping strategies (including attendance at appointments and compliance) and perceived controllability.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, patients who maintain inappropriate beliefs about the timeline of treatment or the curative ability of medications will face difficulties with appropriate adherence. The effect of this discordance was demonstrated in a study which found that patients who believed that hyperlipidemia was a long-term stable disease were more adherent [14]. In another study, 58% of statin users reported not knowing the expected duration of treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Although non-modifiable patient factors such as age, gender, ethnicity, and comorbidity are associated with statin adherence, the relationship has been inconsistent. [13][14][15] Limited understanding of the modifiable patient factors predictive of poor adherence is a key barrier to improving statin adherence. This prospective study was designed to identify potentially modifiable patient factors related to poor adherence.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is these representations that guide how individuals cope with their health problems (7,8). A wealth of literature exists supporting the theory that individual's cognitive and emotional representations about their health problems guide how they cope with those problems (21)(22)(23)(24)(25). In addition, representations have also been shown to predict important health-related outcomes (21,24,(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%